Impact of sarcopenia on prognostic value of cirrhosis: going beyond the hepatic venous pressure gradient and MELD score. Issue 5 (29th October 2018) - Kang, Seong Hee; Jeong, Woo Kyoung; Baik, Soon Koo; Cha, Seung Hwan; Kim, Moon Young
Abstract: Background: Sarcopenia has been reported as a prognostic factor. We evaluated the impact of sarcopenia to the conventional prognostic factors [Model for End‐Stage Liver Disease (MELD) score, Child–Turcotte–Pugh (CTP) score, hepatic venous pressure gradient (HVPG)] in cirrhosis. Methods: Overall, 452 patients with cirrhosis were stratified by MELD score (low < 15, high ≥ 15), CTP class, and HVPG [non‐clinically significant portal hypertension (CSPH), 6–9 mmHg; CSPH, 10–19 mmHg; extremely severe PH, ≥20 mmHg]. L3 skeletal muscle index as marker of sarcopenia was subdivided into quartiles (47.01–52.25–58.22 cm 2 /m 2 ). Results: Among the patients, 42% (190/452) presented with sarcopenia. During a median follow‐up period of 21.2 months, sarcopenia was associated with mortality (adjusted hazard ratio = 2.253, P < 0.001) and specifically with compensated and early decompensated stages of cirrhosis, but not with advanced decompensated stages; low ( P < 0.001) and high ( P = 0.095) MELD scores; CTP classes A ( P = 0.034), B ( P < 0.001), and C ( P = 0.205); and non‐CSPH ( P = 0.018), CSPH ( P < 0.001), and extremely severe PH ( P = 0.846). In quartiles of sarcopenia, MELD score, CTP class, and HVPG were independent predictors of mortality in non‐sarcopenia, but not in severe sarcopenia (MELD, P = 0.182; CTP, P = 0.187; HVPG, P = 0.077). Conclusions: Sarcopenia is associated with mortality in compensated and early decompensated cirrhosis, and existing conventional prognostic factors had limited value in severe sarcopenia. Therefore, incorporating sarcopenia in the conventional prognostic factors had added value, particularly in compensated and early decompensated cirrhosis. Subclassification of prognostic factors according to sarcopenia may help to better assess the prognosis of cirrhosis.